2013
DOI: 10.1016/s0254-6272(13)60123-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of acupoint combinations against deep venous thrombosis in elderly bedridden patients after major surgery

Abstract: Hemorheological indices in postoperative bedridden elderly patients were improved after combined electrical stimulation at Yinlingquan (SP 9) and Sanyinjiao (SP 6). Combined electrical stimulation at Zusanli (ST 36) and Taichong (LR 3), on the other hand, accelerated lower limb venous flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…8,30,33 In addition, acupuncture at ST 36 is also known to reduce sympathetic activity with a decrease in noradrenaline 8,29 ; increase blood flow by increasing eNOS protein and mRNA, and decreasing platelet aggregation (shown by decreases in hydroperoxide and sP-selectin) 3 ; reduce proinflammatory cyto-kine interleukin (IL)-6 and erythrocyte sedimentation rate; increase plasma superoxide dismutase, glutathione reductase catalase activity, glutathione-stimulating hormone, and plasma adenosine triphosphate concentrations; and reduce blood viscosity, plasma viscosity, and d-dimer levels. 38,39 This study used EA because EA parameters can be controlled precisely so the that results can be repeated. EA has been used in many related studies on CVD.…”
Section: Discussionmentioning
confidence: 99%
“…8,30,33 In addition, acupuncture at ST 36 is also known to reduce sympathetic activity with a decrease in noradrenaline 8,29 ; increase blood flow by increasing eNOS protein and mRNA, and decreasing platelet aggregation (shown by decreases in hydroperoxide and sP-selectin) 3 ; reduce proinflammatory cyto-kine interleukin (IL)-6 and erythrocyte sedimentation rate; increase plasma superoxide dismutase, glutathione reductase catalase activity, glutathione-stimulating hormone, and plasma adenosine triphosphate concentrations; and reduce blood viscosity, plasma viscosity, and d-dimer levels. 38,39 This study used EA because EA parameters can be controlled precisely so the that results can be repeated. EA has been used in many related studies on CVD.…”
Section: Discussionmentioning
confidence: 99%
“…De la et al [17] mention that several reports describe Valine 34 Leucine polymorphism as a protective factor against venous and arterial thrombosis. An attempt to prevent DVT using Traditional Chinese Medicine (TCM) in postoperative bedridden elderly patients was reported by Hou et al [18]. The results of the study showed that electrical stimulation of Yinlingquan (SP 9), Sanyinjiao (SP 6), Taichong (LR 3) and Zusanli (ST 36) acupoints increased circulation in the lower limb, thus preventing DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several studies investigating the effect of electrostimulation of venous blood flow, 10,11 data are limited on arterial blood flow. Tucker et al.…”
Section: Discussionmentioning
confidence: 99%